THE EFFECTIVENESS OF USING STORY PYRAMID STRATEGY TOWARD THE STUDENTS’ READING COMPREHENSION - Dwi Kartini Ningsih (Jurnal Bahasa Lingua Scientia, 2015)
Some problems are faced by students in reading of English text. Students are frustrated and bored when they do not understand what they are reading. The interesting strategy is needed to teach them. Story Pyramid Strategy is one of strategies to teach reading comprehension. This strategy forces students to review and summarize the main points of a story. This research is aimed at knowing the effectiveness of using story pyramid strategy in teaching narrative text toward students’ reading comprehension was conducted in this school. The research design of this reseacrh was quasi experimental research with quantitative approach. The research finding in this research showed the difference between the mean of students’ reading score when they are taught without using the story pyramid strategy (73.90) and when they are taught using story pyramid strategy (79.97).  The result of statistical computation using Independent Sample T-Test showed that the score of  tcount was (3.024) and ttable was (2.001). By comparing the “t” was tcount > ttable  known that (3.024 > 2.001). The significant value is 0.004 < 0.05. It was concluded that Story Pyramid Strategy is effective strategy in teaching narrative text toward students’ reading comprehension to junior high school.